Front Cover: Highly Strained Nanoscale Bicyclophane Monolayers Entering the Third Dimension: A Combined Synthetic and Scanning Tunneling Microscopy Investigation (ChemPlusChem 6/2021). Issue 6 (27th April 2021) - Henzel, Sebastian; Becker, Steven; Hennen, Daniel; Keller, Tristan J.; Bahr, Joshua; Jester, Stefan‐S.; Höger, Sigurd
Abstract : The Front Cover shows that the degrees of freedom of the central unit are sterically restricted in the alkoxy‐substituted arylene bicyclophane with a backbone diameter of 0.8 nm. Self‐assembled monolayers form at the interface of graphite and the compound in 1‐phenyloctane. Therein, the molecules arrange in stripes, with the aromatic and topographically extended units appearing bright in the STM image. According to their adsorption geometry, these molecules are attractive platforms for addressing the liquid phase above the solid surface. More information can be found in the Full Paper by S.‐S. Jester, S. Höger, and co‐workers .